Steamboats on the Indus the limits of western technological superiority in South Asia - Dewey, Clive (Oxford University Press, 2014)
Two forms of water-transport competed for supremacy on the Indus and its tributaries in the middle of the nineteenth century: the local country boats and the steamboats imported by the British. Steamboats on the Indus shows that the received wisdom-the 'Technology and Imperialism' school-is wrong to assume that Westerm machines destroyed indigenous techniques wherever they came into competition. Traditional technology could exploit the economic opportunities created by imperialism at lower cost than the most advanced machinery from the West.